A Victorian school and a low carbon designed school: Comparison of indoor air quality, energy performance, and student health. Issue 3 (May 2014) - Chatzidiakou, L.; Mumovic, D.; Summerfield, A. J.; Hong, S. M.; Altamirano-Medina, H.
This paper compares energy and ventilation performance, and levels of pollutants in six school classrooms and associates them to asthmatic and Sick Building Syndrome (SBS) symptoms and the perceived indoor air quality (IAQ) of students. Self-reported data on subjective perception of air quality and health responses were gathered with a standardised questionnaire completed by 151 school children (Response Rate (RR):86%) attending two schools in the Greater London Area: a contemporary suburban low carbon school building and an urban, high thermal mass school built in the 19th century. Temperature, particulate matter (PM), nitrogen dioxide (NO2 ), ozone (O3 ), and volatile organic compounds (VOCs) concentrations were monitored in three classrooms and one outdoor site in each school for 5 consecutive days during the heating seasons. Biological parameters were determined in settled dust and analysed with molecular methods. Overall, asthma prevalence in the school environment was associated with exposure to higher NO2 levels (odds ratio (OR): 1.1, 95% confidence interval (CI): 1.0–1.2). Exposure to PM in all classrooms was high and was associated with increased mucosal symptoms (OR: 1.4, 95% CI: 1.1–1.9) and eczema (OR: 1.3, 95% CI: 1.0–1.6) prevalence. Higher indoor CO2 levels were associated with general symptoms (OR: 1.1, 95% CI: 1.0–1.2). Increased dissatisfaction with IAQ was associated with higher temperatures and exposure to higher NO2, CO2, fungal, cat allergens, and VOC levels (limonene and formaldehyde). Direct access to the playground without buffer zone and user behavioural patterns may affect energy consumption. Findings suggest that increased ventilation rates may mitigate overheating, alleviate SBS symptoms, and improve satisfaction with IAQ.